2022
DOI: 10.3390/cancers14164016
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carbon Nanoparticles in Lymph Node Dissection and Parathyroid Gland Preservation during Surgery for Thyroid Cancer: A Systematic Review and Meta-Analysis

Abstract: Thyroid cancer is the most common endocrine malignancy with an increasing incidence over the past few years. Surgery is considered the primary therapeutic option, which often involves lymph node dissection. The aim of this study was to assess the role of carbon nanoparticles, a novel agent, in thyroid cancer surgery. For that purpose, we conducted a systematic review of the literature on MEDLINE, EMBASE, Scopus, Cochrane and Google Scholar databases from 1 January 2002 to 31 January 2022. Ultimately, 20 articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Therefore, the operation procedure should be strictly observed and conducted to reduce injury to the parathyroid glands during the operation. Where possible, other chromogenic substances, such as Nano-C, can be used to stain the parathyroid gland (25,26). In recent years, fluorescence imaging-relying both on parathyroid gland autofluorescence under near-infrared light-and angiography using the fluorescent dye indocyanine green-has been used to reduce the risk of iatrogenic parathyroid injury during thyroid and parathyroid resections.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the operation procedure should be strictly observed and conducted to reduce injury to the parathyroid glands during the operation. Where possible, other chromogenic substances, such as Nano-C, can be used to stain the parathyroid gland (25,26). In recent years, fluorescence imaging-relying both on parathyroid gland autofluorescence under near-infrared light-and angiography using the fluorescent dye indocyanine green-has been used to reduce the risk of iatrogenic parathyroid injury during thyroid and parathyroid resections.…”
Section: Discussionmentioning
confidence: 99%
“…The study aims to determine whether PET/MRI scans performed after the injection of this experimental tracer are more accurate than standard imaging scans for locating prostate tumour cell masses. The tracer's biodistribution will be monitored, and the use of this tracer in patients undergoing surgery for prostate cancer will be studied for the first time [ 88 ] Targeted Silica Nanoparticles for Real-Time Image-Guided Intraoperative Mapping of Nodal Metastases cRGDY-PEG-Cy5.5 NCT02106598 Patients received standard-of-care technetium Tc 99 m sulfur colloid before receiving an intradermal microdose of integrin-targeting, dye-encapsulated NPs with polyethylene glycol chains on their surfaces. These NPs are called cRGDY-PEG-Cy5.5.…”
Section: Nanotechnology Approaches For Image-guided Surgerymentioning
confidence: 99%
“…Therefore, developing technologies that can make performing this procedure safer and increase the precision of lymph node dissection is a topic of significant interest. Carbon NPs outperformed methylene blue concerning lymph node staining and positive rate for SLN metastatic disease in thyroid cancer surgery [ 88 ]. Other dyes, such as methylene blue and indocyanine green, have been employed to enhance the results of thyroid surgery.…”
Section: Nanotechnology Approaches For Image-guided Surgerymentioning
confidence: 99%
“…Hagiwara et al reported the first series using this technique in thyroid surgery (64). The rate of inadvertent parathyroidectomy was reduced by 34% according to a meta-analysis in 2022 (65).…”
Section: Carbon Nanoparticles In Ln Dissection To Preserve Parathyroi...mentioning
confidence: 99%